1989
DOI: 10.1523/jneurosci.09-05-01731.1989
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of contour perception in monkey visual cortex. I. Lines of pattern discontinuity

Abstract: We have studied the mechanism of contour perception by recording from neurons in the visual cortex of alert rhesus monkeys. In order to assess the relationship between neural signals and perception, we compared the responses to edges and lines with the responses to patterns in which human observers perceive a contour where no line or edge is given (anomalous contour), such as the border between gratings of thin lines offset by half a cycle. With only one exception out of 60, orientation-selective neurons in ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
214
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 507 publications
(233 citation statements)
references
References 29 publications
16
214
1
Order By: Relevance
“…had discovered neural correlates of illusory contours in V2 (but not V I) of macaque monkeys. Subsequent work in the same laboratory extended these original findings, not only establishing the existence of "illusory contour cells," but also providing data on the effect of a variety of parametric stimulus variations on cellular activity (Peterhans & von der Heydt, 1989Peterhans, von der Heydt, & Baumgartner, 1986;von der Heydt & Peterhans, 1989a, 1989b. In all these studies, stimuli consisting of abutting line gratings (Figure 19a) and stimuli consisting of two parallel bars with rectangular notches cut out (Figure 19b) were tested extensively.…”
Section: Alusory Contours As Early Vision Phenomenamentioning
confidence: 89%
“…had discovered neural correlates of illusory contours in V2 (but not V I) of macaque monkeys. Subsequent work in the same laboratory extended these original findings, not only establishing the existence of "illusory contour cells," but also providing data on the effect of a variety of parametric stimulus variations on cellular activity (Peterhans & von der Heydt, 1989Peterhans, von der Heydt, & Baumgartner, 1986;von der Heydt & Peterhans, 1989a, 1989b. In all these studies, stimuli consisting of abutting line gratings (Figure 19a) and stimuli consisting of two parallel bars with rectangular notches cut out (Figure 19b) were tested extensively.…”
Section: Alusory Contours As Early Vision Phenomenamentioning
confidence: 89%
“…Given the well-known ordering of ascending visual projections (e.g., retina, LGN, V1, V2, ... IT) and the discovery of the locus of cells that are relevant to depth and constancy processing (e.g., the cells in V2 that von der Heydt and Peterhans (1989) identified that respond to illusory contours), it is tempting to try to translate the terms "early" and "late" directly into physiological descriptions, such as "before V2" and "after V2." The problem is that the well documented, massive, backward connections from higher levels to lower levels throughout the visual system make such translations difficult, if not impossible.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Studies on visual contour processing have demonstrated that neurons in V1 are responsive to real luminance-defined contours, whereas neurons in V2 can recognize ''higher-order'' illusory contours (e.g., refs. [32][33][34][35]. In a similar vein, in this study, we compared V1 and V2 response with real and illusory brightness modulations.…”
mentioning
confidence: 99%